From histology to sonography in synovitis: EURO-MUSCULUS/USPRM approach - Ricci, Vincenzo; Ricci, Costantino; Tamborrini, Giorgio; Chang, Ke-Vin; Mezian, Kamal; Zunica, Fiammetta; Naňka, Ondřej; Kara, Murat; Özçakar, Levent (Pathology, research and practice, 2023)
OBJECTIVES: The aim of the present study was to propose a methodologically innovative sonographic approach for optimal evaluation of synovial tissues (starting from histopathology). METHODS: Using high-frequency ultrasound probes and high-level ultrasound machines, we matched the histological microarchitecture of synovial tissues with multiple sonographic patterns in physiological and pathological conditions. Likewise, high-sensitive color/power Doppler assessments have also been performed to evaluate the microcirculation. RESULTS: Modern equipment allows for a macroscopic classification of synovial pathologies recognizing different morphological patterns; however, intimal and subintimal layers of the synovium cannot be distinguished from each other on ultrasound. High-sensitive Doppler imaging clearly defines the microvascular pattern, especially in patients with hypertrophic synovial pathologies. CONCLUSIONS: In clinical practice, using adequate technological equipment i.e. high-frequency B-mode and high-sensitive Doppler imaging, detailed sonographic assessment of synovial tissues can be performed - defining the main sono-histological patterns.
Keywords: Synovitis; Muscles; Synovial Membrane; revmatoidní artritida; Ultrasonography; ultrasonografie; Humans; synoviální membrána; lidé; synovitida; svaly; Arthritis, Rheumatoid